2014
DOI: 10.1017/s1368980014002729
|View full text |Cite
|
Sign up to set email alerts
|

Association between household food access insecurity and nutritional status indicators among children aged <5 years in Nepal: results from a national, cross-sectional household survey

Abstract: Objective: To examine the association between household food insecurity score and Z-scores of childhood nutritional status indicators. Design: Population-based, cross-sectional survey, Nepal Demographic and Health Survey 2011. Setting: A nationally representative sample of 11 085 households selected by a two-stage, stratified cluster sampling design to interview eligible men and women. Subjects: Children (n 2591) aged 0-60 months in a sub-sample of households selected for men's interview. Results: Prevalence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
24
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 29 publications
7
24
3
Order By: Relevance
“…Non-validation of modified HFIAS (7-items and 12 months recall period) and extending the period of recall from 30 days to adjust for seasonal variations in food supply in Nepal may have resulted in underestimation of HFI in NDHS 2011. Reporting biases of tobacco use, HFI due to cultural barriers and stigma have been discussed in detail elsewhere [34]. Notwithstanding above limitations, our study further strengthens the reported association of adult tobacco use with HFI, highlighting the previously less recognised non-health consequences of tobacco use on the poor households.…”
Section: Discussionsupporting
confidence: 79%
“…Non-validation of modified HFIAS (7-items and 12 months recall period) and extending the period of recall from 30 days to adjust for seasonal variations in food supply in Nepal may have resulted in underestimation of HFI in NDHS 2011. Reporting biases of tobacco use, HFI due to cultural barriers and stigma have been discussed in detail elsewhere [34]. Notwithstanding above limitations, our study further strengthens the reported association of adult tobacco use with HFI, highlighting the previously less recognised non-health consequences of tobacco use on the poor households.…”
Section: Discussionsupporting
confidence: 79%
“…In adolescence, there is an increased demand for nutrients due to growth spurt and to attain puberty [3]. Studies have reported that food insecurity at adolescent stage (10)(11)(12)(13)(14)(15)(16)(17)(18)(19) years of age) can affect their linear growth [4], high risk of involving in violence perpetration [5] and are twice likely to develop cardiovascular diseases (2.27; 95% confidence interval [CI], 1.61-3.21) [6].…”
Section: Introductionmentioning
confidence: 99%
“…It also has serious consequences for wellbeing. HFI is associated with adverse nutritional, physical and mental health outcomes for both children and adults [4,[6][7][8][9]. While all food insecurity is concerning, the implications for women of childbearing age are particularly acute due to the potential for intergenerational consequences.…”
Section: Introductionmentioning
confidence: 99%
“…HFI also adversely affects child wellbeing. Children from food insecure homes are more likely to suffer from stunting, underweight, and wasting [7][8][9][22][23][24][25]. In rural Indonesia, HFI was correlated with higher neonatal, infant and under-five child mortality [26].…”
Section: Introductionmentioning
confidence: 99%